Upaya Pengembangan Motorik Kasar Melalui Kegiatan Menari Di RA Imama Kedungpane Mijen Semarang - Mursid Mursid; Syafa’atun Nabilah (Journal of Early Childhood and Character Education, 2021)
Dancing is one of the most interesting activities for children and can develop children's gross motor skills in a fun way. The fact that the high and low gross motor skills of the children are caused by the activities given by the teacher are less interesting, they do more fine motor activities compared to gross motor activities. This study aims to determine gross motor development through dance activities in group B1 at RA IMAMA Kedungpane Mijen Semarang.This research method is classroom action research (CAR) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation and reflection. This research was conducted with a total of 27 children. The instrument of this research is using observation guide and documentation guide.The results of the study concluded that: in the pre-action research, the results were 32.22%, then in the first cycle there was an increase in the average gross motor development reaching 55.74% and the second cycle the average gross motor development reaching 84.44%. This research is successful because it has reached the research indicator target of 75%.